The Development of Mathematics Teaching Materials through Geogebra Software to Improve Learning Independence - Saputra, Eri; Fahrizal, Effan (Universitas Malikussaleh, Aceh Utara, Indonesia, 2019)
Geogebra is software designed to solve geometry, calculus and algebra material as well as applications for designing spaces and buildings. The purpose of this research is to produce teaching material products through Geogebra software in mathematics courses that can be utilized in learning. The stages in this research include: (1) the stage of developing teaching material products, (2) the testing phase of teaching materials products (3) the analysis of increasing student’s independence. Product development and level of practicability of teaching materials is validated by material experts, media experts, lecturers as users, and trials of teaching material products. Qualitative data is used as a consideration in teaching material products to make revisions while quantitative data is analysed by statistical tests to see an increase in student self-independence. Based on the test results of experts teaching materials developed for trials in the field. Experts recommendations about teaching materials are appropriate for use and revision. After the revision is issued, try the field that involving students, the results of the test items about the reliability level of 0.734 so that teaching materials could be used for research instrumentts. The average value and standard deviation of the normalized gain values for the experimental class are 0.812 and 0.139 while the control class are 0.731 and 0.198. The analysis result of the questionnaire is that there is an increase in self-independence in study of the students in Architecture Study Program, Engineering Faculty, Malikussaleh University.